Learning by leading: A qualitative inquiry into the perceived academic, personal, and professional development of PAL study group leaders in physiotherapy education. - Christensen, Lene; Hilde, Gunvor; Eik, Hedda (Physiotherapy Theory & Practice, 2025)
Background: Peer assisted learning (PAL), where student leaders facilitate their peers' learning, is prevalent in higher education. However, PAL leaders' development in physiotherapy education and their role perceptions relating to their future professional practice are understudied. Purpose: We aimed to understand how PAL leaders in physiotherapy education perceive their own academic learning and personal development, and how they view their experiences as PAL leaders in relation to future physiotherapy practice. Methods: Focus group interviews were used to collect qualitative data from third-semester students who had been PAL leaders (n = 19). Data were analyzed using a reflexive, thematic analysis. Results: Three main themes were generated: "Being a PAL leader consolidates knowledge and facilitates new learning," "Personal growth through experiential learning outside the comfort zone within a community of practice," and "Learning by leading – transferability of being a PAL leader to future physiotherapy practice." Conclusion: Overall, physiotherapy students leading PAL study groups demonstrated academic, personal, and professional growth via experiential learning in a community of practice. They developed skills likely transferable into their future physiotherapy roles. Our findings propose PAL study groups as an arena for PAL leaders to practice complex physiotherapy competences, positioning PAL study groups as valuable preclinical practice for physiotherapy students.